Entangle, Entangled, Entanglements: Reimagining a Child and Youth Engagement Model Using a Common Worlds Approach - Caputo, Virginia (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2022)
This paper responds to the call to explore pedagogical relations and dialogues in considering how to create climate pedagogies that are responsive, dynamic, and transformative in thinking about human and nonhuman relations. Using the lens of entanglement, the paper attempts to bring into dialogue children’s rights and more-than-human ways of thinking to understand what, if any, commonalities lie in these two projects and whether and how a rights-respecting approach can be productively reconfigured in envisaging a dynamic climate pedagogy. It considers several tensions that arise from this entangled dialogue to probe both the overlaps and points of incommensurability in the two approaches. This includes viewing asymmetrical power and logics of coloniality that assert themselves through rights discourses and rights-based techniques based in an Anglo-Eurocentric worldview that narrowly defines who is included in the “human” of human rights. To illustrate these entanglements, the paper draws on a child/youth-led and child/youth-driven participatory model called Shaking the Movers (STM) created in 2007 by the Landon Pearson Centre and used with youth as well as with children in early childhood and other settings across Canada each year. The model aims to enable children’s civil and political rights. Shaking the Movers was used as the framework for a workshop held in Williams Lake, British Columbia in 2017. The workshop serves as a case study in this paper to illustrate some of the entanglements that arise in practice when considering rights-respecting and more-than-human approaches. The analysis draws on scholarship from several disciplinary locations, including Stuart Aitken’s critical childhood concept of the post-child, Veronica Pacini-Ketchabaw and Affrica Taylor’s notion of agency as not exclusively human and conceived as collective rather than an outcome of individual intent, and Shenila Khoja-Moolji’s analysis of an ethic of interdependency and alliance when understanding human rights in context. Each of these perspectives informs a contemplation of how to reconfigure the Shaking the Movers model amplify its strengths. The paper concludes with thoughts on the ways entanglements create a productive space both for bringing together a more-than-human and rights-respecting approach to attend to actions emanating from the margins and for invigorating and understanding how to meaningfully engage children located in interconnected and interdependent worlds.